Nigeria : Strengthening Monetary and Liquidity Management - International Monetary Fund (World Bank, Washington, DC, 2013)
The 2002 Financial Sector Assessment Program (FSAP) identified considerable problems in containing the upsurge in liquidity in the financial system, partly caused by spending of oil receipts. In the face of persistent excess liquidity in the financial system, the Central Bank of Nigeria (CBN) made numerous adjustments in the monetary policy framework and instruments; however, these had a limited impact on monetary aggregates. A structural excess liquidity is a common feature in oil exporting countries like Nigeria because of sustained large foreign currency inflows. This note reviews the current frameworks for monetary policy and liquidity management and discusses role of selective financial markets in improving liquidity management in Nigeria. It also provides some recommendations to further strengthen the implementation of monetary policy, particularly systemic liquidity management. This note is structured as follows: chapter one gives context and background; chapter two gives monetary policy framework; chapter three presents liquidity forecasting and management; chapter four gives functioning of financial markets and liquidity management; and chapter five gives recommendations.